Consensus Optimization for Energy Efficiency in Heterogeneous Wireless Sensor Networks: Models, Techniques, and Future Directions - Matthew Iyobhebhe; Abdoulie Momodou. S Tekanyi; Elvis Obi; Shamsudeen. A. Mikail; Botson Ishaya Chollom; Paul Thomas Muge; Athanisius Terlumun Utev; Ridwan. O Eleshin; Fatima Ashafa (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2026)
Energy efficiency continues to be a major concern in heterogeneous wireless sensor networks (HWSNs) due to unequal resource allocation and varying network dynamics. Consensus optimisation offers an effective paradigm for enabling distributed management and achieving balanced energy utilisation among heterogeneous sensor nodes. This review presents an in-depth examination of consensus-based models and techniques aimed at improving energy efficiency in HWSNs. It categorises existing methodologies based on their operational mechanisms and analyses how node heterogeneity impacts consensus formulation and overall network performance. In addition, it highlights key research limitations, including the lack of standardised classifications, inconsistent energy modelling, insufficient benchmarking, and limited analysis of the tradeoff between convergence and energy overhead. By synthesising advances in adaptive weighting, clustering mechanisms, and hierarchical consensus architectures, the study proposes future research pathways for scalable, robust, and energy-efficient consensus systems. Ultimately, this review provides a foundation for developing sustainable optimisation frameworks for next-generation sensor networks.